Sosialisasi Pluralitas Agama Dalam Konteks Hukum - Tomy M Saragih (Jurnal Risalah Hukum, 2010)
The state seems only sensitive to religion plurality when SARA-induced events occur. It is also weak when it is expected to deal with religion issues, especially those culminated at SARA induced-events. The state may be mandated to solve the law problems as quickly as possible. A solution may be through the socialization method over religion plurality through legal officer to improve the sense of mutual respect among citizens. The self-judging action, therefore, can be prevented.